Upper Secondary School Teachers' Digital Competence: Analysed by Demographic, Personal and Professional Characteristics - Rune Johan Krumsvik; Lise Øen Jones; Marianne Øfstegaard; Ole Johan Eikeland (Universitetsforlaget, 2016)
Educational technology provides an opportunity to improve the quality of education. There is, however, a lack of uptake in utilizing the equipment provided, as well as a lack of well-established methods for monitoring the use of educational technology. In this paper, which is based on one of the largest ICT studies in secondary schools in Norway, we explore the relationship between upper secondary school teachers' digital competence analysed by demographic, personal and professional characteristics. The implications of this study are that demographic, personal and professional characteristics, such as a teacher's age, work experience, gender, screen time and ICT education, predict teachers' high or low digital competence in upper secondary school to a certain degree. Further research is recommended in order to validate these preliminary findings.